The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.foodchem.2016.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between major chlorogenic acid isomers and chemical changes in coffee brew that affect antioxidant activities

Abstract: Coffee bean source and roasting conditions significantly (p<0.05) affected the content of chlorogenic acid (CGA) isomers, several indices of browning and subsequent antioxidant values. Principal component analysis was used to interpret the correlations between physiochemical and antioxidant parameters of coffee. CGA isomer content was positively correlated (p<0.001) to capacity of coffee to reduce nitric oxide and scavenge Frémy's salt. Indices of browning in roasted coffee were positively correlated (p<0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
1
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 35 publications
(35 reference statements)
7
45
1
10
Order By: Relevance
“…The higher activity to decrease ROS generation showed DiRCE. The results confirmed the observations made by Liang et al, who suggested on the basis of PCA analysis that dichlorogenic acids exhibit high potential to scavenge intracellular ROS [36].…”
Section: Effect Of Coffee Extracts On Viability and Level Of Intracelsupporting
confidence: 91%
“…The higher activity to decrease ROS generation showed DiRCE. The results confirmed the observations made by Liang et al, who suggested on the basis of PCA analysis that dichlorogenic acids exhibit high potential to scavenge intracellular ROS [36].…”
Section: Effect Of Coffee Extracts On Viability and Level Of Intracelsupporting
confidence: 91%
“…Tabel 5 menunjukkan nilai konstanta laju reaksi (k) asam korogenat lebih besar dibandingkan nilai k kafein pada ketiga suhu yang diuji, walaupun energi aktivasi asam klorogenat sedikit lebih rendah dibandingkan kafein.. Hasil yang sama didapatkan oleh (JeszkaSkowron, Sentkowska, Pyrzyńska, & De Peña, 2016), pengukusan biji kopi Robusta Indonesia dengan air panas 94 °C mendapatkan penurunan asam klorogenat yang signifikan. Selanjutnya (Liang, Xue, Kennepohl, & Kitts, 2016), menyatakan bahwa asam klorogenat dan isomernya mudah terurai menjadi senyawa radikal bebas lain bila diolah dengan suhu tinggi termasuk penyangraian.…”
Section: Kandungan Asam Klorogenat Biji Kopi Hasil Pengukusanunclassified
“…The assays of offline DPPH radical scavenging activity were performed according to previously reported protocols [17]. Ascorbic acid (VC) was used as positive control.…”
Section: Dpph Radical Scavenging Activity Assaysmentioning
confidence: 99%